Antioxidant Capacities of Holothuria Sea Cucumbers - Murniasih, Tutik; Putra, Masteria Yunovilsa; Pangestuti, Ratih (Annales Bogorienses, 2015)
Sea cucumbers are a potential source of biologically active metabolites that are widely used for nutraceutical, pharmaceutical and cosmeceutical products. In this study we investigated the antioxidant activity of several extracts of sea cucumbers, those are Holothuria scabra, Holothuria atra, Holothuria leucospilota, and Holothuria excellens collected from Lombok Island. The selected sea cucumber was then separated to get the active fractions and identified for profiling the secondary metabolites. Phytochemical screening reveals the presence of flavonoid, terpenoids, phenol, saponin, alkaloid, anthraquinone, and glycoside in the extracts of Holothuria sea cucumbers. Radical scavenging effects on the DPPH (1,1-diphenyl-2-picryl-hydrazyl) model were evaluated. The previous work reported that the crude extract of H. atra showed the highest potential of antioxidant capacity. H. atra extract was separated by column chromatography on silica gel and eluted with a gradient system of increasing polarity. Fraction 7 of H. atra extract showed significantly inhibited radical scavenging activity (35.3487 %) at concentration 1 mg/ml. The result of Gas Chromatography-Mass Spectrometry analysis of H. atra fraction 2 showed that it has several active antioxidant compounds which are ethyl cetylate (3), hexadecyl-oxirane (5), 3-chloro-4-hydroxybenzoic acid (6), andoleyl alcohol, trifluoroacetate (9). Moreover, the active fraction 7 indicated several compounds, those are cycloicosane (17), pentadecyl trichloroacetate (18), 14b-pregnane (21) and cis-4-yano-2-(2-hydroxycyclohexyl) pyridine. However, these are preliminary findings and further studies are needed to be focus on the purifications of unknown compounds and formulation for nutraceuticals.